PSIKOEDUKASI KESEHATAN MENTAL PADA KELAS XI SMA AL-ISLAM 1 SURAKARTA SEBAGAI BENTUK PENGABDIAN KEPADA MASYARAKAT - Sukamto, Ika Sumiyarsi; Sigalingging, Lidya Diantika; Hanum, Annisa Lutfia; Subekti, Aditya Farit; Azizah, Rania; Wulandari, Reza Sefty (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
This community service activity aims to improve students’ understanding of mental health through psychoeducational interventions. The participants were eleventh-grade students of SMA Al-Islam 1 Surakarta. The method employed was a quasi-experimental design with a pretest-posttest group design. The intervention was conducted through interactive mental health counseling supported by posters as visual media. The pre-test results showed an average score of 83.16, while the post-test average increased to 94.71. Thus, there was an improvement of 11.55 points after the intervention. These findings indicate that psychoeducation is effective in enhancing students’ understanding of stress factors, stress management strategies, and the importance of maintaining mental health in daily life.